Gd-Co BASED METAL POWDER, METHOD FOR PRODUCING THE SAME, CONDUCTIVE MOLDING, AND THERMOELECTRIC CONVERSION ELEMENT
The GD-CO-based metal powder technology addresses the challenge of achieving high Nernst coefficients in zero magnetic fields and cost-effective production of thermoelectric conversion elements in diverse shapes and sizes, enhancing their industrial applicability.
Patent Information
- Application Number
- JP2024111091
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-07-10
- Publication Date
- 2025-02-05
AI Technical Summary
Existing thermoelectric conversion elements face challenges in achieving high Nernst coefficients in zero magnetic fields and are costly or difficult to produce in various shapes and sizes, limiting their industrial application in small-sized devices and sensors.
A GD-CO-based metal powder with specific particle size distribution and magnetic properties is used to create conductive forms like sintered bodies, ensuring high Nernst coefficients in zero magnetic fields and enabling production of thermoelectric conversion elements in diverse shapes and sizes.
The GD-CO-based metal powder technology provides thermoelectric conversion elements with high Nernst coefficients and resistance to external magnetic fields, offering improved cost-effectiveness and versatility in producing elements of varied sizes and shapes.
Smart Images

Figure 2025017331000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a Gd-Co based metal powder useful as a material for a thermoelectric conversion element, and a method for producing the same, and also to a conductive compact of the Gd-Co based metal powder, and a thermoelectric conversion element using the conductive compact. [Background technology]
[0002] In recent years, research has been conducted into thermoelectric conversion elements that utilize the anomalous Nernst effect. The anomalous Nernst effect is a phenomenon in which, when a heat flow perpendicular to the magnetization is applied to a spontaneously magnetized magnetic material, an electromotive force is generated in a direction perpendicular to both the magnetization and the heat flow. The anomalous Nernst effect allows current to be extracted perpendicular to the heat flow, which is an advantage over the Seebeck effect in that it allows the construction of thin, sheet-like thermoelectric conversion devices. For example, the ferromagnetic intermetallic compound Co2MnGa is known as a material that exhibits a large anomalous Nernst effect at room temperature.
[0003] Patent Document 1 describes an experimental example in which a Co2MnGa single crystal was produced by the Czochralski method and the anomalous Nernst coefficient was measured. The Nernst coefficient of a Co2MnGa single crystal at room temperature (300K) reaches a high value of about 6μV / K regardless of whether the magnetic field direction is parallel to the
[0100] ,
[0110] , or
[0111] direction of the crystal (paragraph 0021, Figure 4).
[0004] Patent Document 2 describes the use of an anomalous Nernst material film in a composite sensor having a heat flow sensor and a temperature sensor. Several substances are listed as anomalous Nernst materials (paragraph 0026). A sputtering method is shown as a method for forming the anomalous Nernst material film (paragraph 0030).
[0005] Major applications of thermoelectric conversion elements include thermoelectric power generation devices and heat flow sensors.
[0006] It is desirable for the thermoelectric conversion element to realize a thermoelectric power generation device to be a bulk body with a thickness of about several millimeters. It is possible to produce a bulk body of the above size by using a single crystal body by the Czochralski method. However, single crystal manufacturing techniques such as the Czochralski method are high cost and low productivity, so they are not practical for industrial production of materials for thermoelectric power generation devices. On the other hand, it is difficult to apply film formation techniques such as the sputtering method to the industrial production of bulk materials for thermoelectric power generation devices.
[0007] Considering that the thermoelectric conversion element for realizing the heat flow sensor is to be incorporated into a part of a minute circuit pattern, it is desirable that the element be small in size. It is difficult to industrially put into practical use in terms of cost to cut out a large number of small-sized elements from a single crystal obtained by the Czochralski method or the like. It is also difficult to directly form small-sized elements of a predetermined shape by the Czochralski method. On the other hand, according to a film formation technique such as a sputtering method, it is possible to directly form small-sized elements corresponding to a predetermined circuit pattern on an insulating substrate. However, such a film formation method has low productivity, and the manufacturing cost of the heat flow sensor is high.
[0008] Patent Document 3 discloses a powder of Co2MnGa as a material that can be widely used to manufacture thermoelectric conversion elements of various shapes and sizes. A conductive compact using this powder has a high Nernst coefficient similar to that of single crystal Co2MnGa.
[0009] On the other hand, Patent Document 4 describes that antiferromagnetic Mn3Sn powder exhibits a coercive force of about 0.25 to 0.5 T and exhibits a thermoelectric conversion action due to the anomalous Nernst effect even in a state where no magnetic field is applied (hereinafter, this may be referred to as "zero magnetic field"). [Prior art documents] [Patent documents]
[0010] [Patent Document 1] International Publication No. 2019 / 009308 [Patent Document 2] JP 2020-153668 A [Patent Document 3] Patent Publication No. 2023-2425 [Patent Document 4] JP 2021-145116 A Summary of the Invention [Problem to be solved by the invention]
[0011] Currently, materials that exhibit a high Nernst coefficient, such as the above-mentioned Co2MnGa, are known. However, since Co2MnGa has poor coercive force, it is almost impossible to obtain thermoelectric conversion action due to the anomalous Nernst effect when no magnetic field is applied (zero magnetic field). Thermoelectric conversion elements used in sensors are expected to be installed in small spaces inside electronic devices, and it is practically difficult to implement thermoelectric conversion elements in devices together with powerful magnets. For this reason, it is desirable to use materials that exhibit thermoelectric conversion action even in zero magnetic field for thermoelectric conversion elements.
[0012] On the other hand, if the Mn3Sn powder disclosed in Patent Document 4 is used, it is possible to obtain a thermoelectric conversion effect even in a zero magnetic field. However, its Nernst coefficient is considerably smaller than that of Co2MnGa, and is not sufficient for constructing a practical thermoelectric conversion element. In addition, the coercive force of Mn3Sn powder is said to be about 0.25 to 0.5 T (Patent Document 4), but in order to provide the reliability of a stable and high thermoelectric conversion effect even when exposed to disturbances such as magnetic fields generated by equipment, it is desirable to develop an anomalous Nernst effect-producing material with an even higher coercive force.
[0013] The present invention aims to provide a new material that has a high coercive force, exhibits a high Nernst coefficient in zero magnetic field, and is easily applicable to the manufacture of thermoelectric conversion elements of various shapes and sizes, and also aims to provide a thermoelectric conversion element with a high Nernst coefficient obtained by using the material. [Means for solving the problem]
[0014] In order to achieve the above object, the present specification discloses the following invention.
[0015] [1] A powder containing the intermetallic compound GdCo5 as a main component, in which the cumulative 50% particle diameter D50 is 1 to 150 μm and the cumulative 90% particle diameter D90 is 250 μm or less in a volume-based particle size distribution measured by a laser diffraction / scattering method. [2] A process for producing an alloy ingot by solidifying molten metal of a Gd-Co alloy to obtain an alloy ingot mainly composed of the intermetallic compound GdCo5; a crushing step of crushing the alloy block to obtain a powder; The method for producing a metal powder according to the above [1]. [3] A conductive powder compact whose main component is the intermetallic compound GdCo5. [4] The conductive molded body according to the above [3], wherein the powder containing the intermetallic compound GdCo5 as a main component has a cumulative 50% particle diameter D50 of 1 to 150 μm and a cumulative 90% particle diameter D90 of 250 μm or less in a volume-based particle size distribution measured by a laser diffraction / scattering method. [5] The conductive molded body according to [3] or [4] above, which is a sintered body of a powder containing the intermetallic compound GdCo5 as a main component. [6] The conductive molded article according to any one of the above [3] to [5], which exhibits a Nernst coefficient of 0.2 μV / K or more at a temperature of 300 K in the absence of an applied magnetic field. [7] A thermoelectric conversion element using the conductive molded article according to any one of the above [3] to [6]. Effect of the Invention
[0016] According to the present invention, it is possible to obtain a thermoelectric conversion element that exhibits a high Nernst coefficient in zero magnetic field and has excellent resistance to disturbances caused by external magnetic fields. Since the material used for the thermoelectric conversion element is a powder, the technology of the present invention can be widely applied to elements of various shapes and sizes. Furthermore, the technology of the present invention is superior in terms of cost and productivity compared to technologies that use single crystals or thin films produced by sputtering. [Brief description of the drawings]
[0017] [Figure 1] SEM photograph of Gd-Co-based metal powder ground using a hammer mill. [Diagram 2] SEM photograph of Gd-Co-based metal powder, which was crushed using a sample mill. [Diagram 3] SEM photo of Gd-Co based metal powder ground using a planetary ball mill. [Figure 4] 2 is a graph illustrating particle size distribution curves of the Gd—Co-based metal powder obtained in Example 1, which is crushed by a hammer mill, a sample mill, and a planetary ball mill. [Diagram 5] FIG. 2 is a diagram illustrating X-ray diffraction patterns of the Gd—Co-based metal powder obtained in Example 1, which was ground by a hammer mill, a sample mill, and a planetary ball mill. [Figure 6] 2 is a graph illustrating magnetization curves of the Gd—Co-based metal powder obtained in Example 1, which is ground by a hammer mill, a sample mill, and a planetary ball mill. [Figure 7] This is a schematic diagram showing the positions of the terminals for power measurement and the probes for temperature measurement, as well as the directions of heat flow and magnetic field application for a sample for measuring the Nernst effect. [Figure 8] Graph showing the measurement results of the Nernst coefficient for a conductive compact of GdCo5 powder, which is a sample mill pulverized product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [Gd-Co metal powder] In the present invention, a Gd-Co based metal powder containing the intermetallic compound GdCo5 as a main component is used as a material suitable for thermoelectric conversion elements. The intermetallic compound GdCo5 has a hexagonal crystal structure and exhibits antiferromagnetism at room temperature.
[0019] In a composition range where the composition ratios of Gd (gadolinium) and Co (cobalt) are close to the stoichiometric composition of GdCo5, an intermetallic compound having a GdCo5-type crystal structure can stably exist as a single phase. It is considered that a Gd-Co alloy in which an intermetallic compound phase having a GdCo5-type crystal structure and a different phase coexist can be obtained around the composition range. Even if the composition deviates slightly from the stoichiometric composition of GdCo5, a crystal phase having a GdCo5-type crystal structure (that is, a crystal structure in which diffraction peaks corresponding to the diffraction peaks from each crystal plane of the GdCo5 crystal of the stoichiometric composition are observed in the X-ray diffraction pattern) is included in the "intermetallic compound GdCo5" referred to in this specification.
[0020] The "powder mainly composed of the intermetallic compound GdCo5" means that in the X-ray diffraction pattern of the powder, when the integrated intensity of the diffraction peak with the highest peak height among the diffraction peaks of the GdCo5-type crystal structure is I0 and the integrated intensity of the diffraction peak with the highest peak height among the diffraction peaks of the different phase (a phase other than the crystal phase of the GdCo5-type crystal structure) is I1, it is a powder for which the relationship I1 < I0 holds. Here, when no different phase is detected, I1 = 0, and the above relationship I1 < I0 is satisfied. In a thermoelectric conversion element using a powder mainly composed of the intermetallic compound GdCo5, even if a different phase other than the GdCo5 phase is included, a thermoelectric conversion action due to the abnormal Nernst effect of the GdCo5 phase occurs. However, in order to realize good thermoelectric conversion characteristics, it is desirable that the abundance of the different phase that does not exhibit the abnormal Nernst effect is small. For example, it is more preferable that I1 < 0.5I0, and it is even more preferable that I1 < 0.3I0. Particularly preferable powders include powders of a GdCo5 single phase in which no different phase is detected.
[0021] The particle size distribution of the particles constituting the Gd-Co-based metal powder is in the range of 1 μm or more and 150 μm or less, and 250 μm or less of cumulative 90% particle size D90 in the volume-based particle size distribution by the laser diffraction scattering method. If the cumulative 50% particle size D50 is too large, the average particle size becomes large, which leads to a decrease in coercivity. If the cumulative 90% particle size D90 is too large, the proportion of coarse particles increases, which also leads to a decrease in coercivity. The optimal particle size distribution conditions vary depending on the application and the manufacturing process of the element, but the optimal conditions can usually be set within the above particle size distribution range. From the viewpoint of emphasizing the securing of coercivity, the cumulative 50% particle size D50 is preferably 70 μm or less, more preferably 50 μm or less, and even more preferably 20 μm or less. Furthermore, the cumulative 90% particle size D90 is preferably 150 μm or less, more preferably 120 μm or less, and even more preferably 60 μm or less.
[0022] The method for producing the Gd-Co based metal powder is, for example, A process for producing an alloy ingot by solidifying a molten metal containing Gd and Co to obtain an alloy ingot mainly composed of the intermetallic compound GdCo5; a crushing step of crushing the alloy block to obtain a powder; A process having the following structure can be applied. If necessary, a classification step of classifying the powder obtained in the pulverization step using a sieve or the like; may be further carried out.
[0023] The molten metal of the Gd-Co alloy can be obtained by, for example, melting the raw metals Gd and Co weighed to a predetermined composition by a plasma arc or by heating and melting them in a crucible. The molten metal is solidified to obtain an alloy ingot mainly composed of the intermetallic compound GdCo5. Since the intermetallic compound GdCo5 is relatively brittle, the alloy ingot can be powdered by mechanical crushing means. For example, the desired particle size can be adjusted using known crushing means such as a hammer mill, a sample mill, or a planetary ball mill. In addition, the powder obtained by the crushing means can be classified by a sieve to adjust the final particle size distribution. The Gd-Co based metal powder of the present invention can be used as a material for a thermoelectric conversion element.
[0024] [Conductive molding] In this specification, an object formed into a predetermined shape using powder as a material and having a definite shape that allows it to maintain its shape in the usage environment is called a "powder compact." In particular, a powder compact having electrical conductivity is called a "conductive powder compact." A conductive powder compact using the above-mentioned Gd-Co-based metal powder as a material and containing the intermetallic compound GdCo5 as a main component is useful as a thermoelectric conversion element.
[0025] Representative forms of the conductive powder compact include a compact and a sintered body. Even if it is a compact, it can be used as a thermoelectric conversion element by incorporating it into a device so that it can maintain its shape in the usage environment. In order to ensure stable shape, a sintered body is preferable.
[0026] As a form of the conductive powder compact other than the pressed powder and sintered body, for example, a compact obtained by solidifying the powder into a predetermined shape with a binder component such as a resin can be mentioned. When a non-conductive binder component is used, the powder particles need to be solidified in a state of contact with each other. When a conductive binder component is used, the powder particles do not necessarily need to be in contact with each other.
[0027] When a sintered body is applied as a conductive compact of a powder mainly composed of the intermetallic compound GdCo5, a known sintering method can be used to prepare a sintered body of a powder mainly composed of the intermetallic compound GdCo5. When a part or all of a circuit pattern formed on an insulating substrate is used as a conductive compact of a powder mainly composed of the intermetallic compound GdCo5, a method of forming a coating film of the circuit pattern on an insulating substrate with a paint containing the powder as a filler, and then heating and sintering the coating film can be applied.
[0028] By using Gd-Co-based metal powder adjusted to the particle size distribution described above as the material, it is possible to construct a conductive molded body that has a large coercive force and exhibits excellent thermoelectric conversion properties in a zero magnetic field environment at room temperature. EXAMPLES
[0029] [Example 1] (Preparation of alloy ingot) The raw materials, metallic Gd (manufactured by Nippon Yttrium Co., Ltd., purity 3N) and metallic Co (manufactured by Rare Metallic Co., Ltd., purity 3N), were weighed out so that the atomic ratio of Ga:Co was 1.0:5.0. Molten Ga-Co alloy metal was produced in an argon atmosphere using an arc melting furnace (manufactured by Nisshin Giken Co., Ltd.). It was then solidified on a water-cooled copper plate to obtain an alloy ingot of approximately 50 g.
[0030] (Powder preparation) The obtained alloy ingot was coarsely crushed in a mortar in a glove box with a nitrogen atmosphere. The crushed product at this stage is called the "coarsely crushed product." The following three types of crushed products were produced using this coarsely crushed product.
[0031] (i) Hammer mill crushed products The coarsely pulverized product was pulverized in the glove box using a hammer mill (Hammer Crusher NH-34S, screen mesh: 0.3 mm, manufactured by Sansho Industry Co., Ltd.) to obtain a hammer mill pulverized product. An SEM (scanning electron microscope) photograph of the hammer mill pulverized product is shown in Figure 1. The SEM used was an FE-SEM JSM-7200F manufactured by JEOL Ltd. (the same applies to each of the following pulverized products). The hammer milled product was subjected to elemental analysis using an EDX (energy dispersive X-ray analysis) device (X-Max20, manufactured by Oxford Instruments) attached to the SEM (the same was done for each of the following crushed products). As a result, the composition of the hammer milled product was Ga:Co=1.2:5.0 in atomic ratio, and the oxygen content was 1.0 mass%. In addition, the particle size distribution of the hammer milled product was measured using a dry laser diffraction particle size distribution analyzer (HELOS & RODOS, manufactured by Japan Laser Co., Ltd.) with a lens with a focal length of 200 mm (the same was true for each of the following crushed products). As a result, the volume-based cumulative 10% particle diameter D10 of the hammer milled product measured by the laser diffraction / scattering method was 5 μm, the cumulative 50% particle diameter D50 was 44 μm, and the cumulative 90% particle diameter D90 was 111 μm.
[0032] (ii) Sample mill crushed product A part of the above hammer mill ground product was ground in the glove box with a sample mill (SK-M10 model, manufactured by Kyoritsu Riko Co., Ltd.) to obtain a sample mill ground product. FIG. 2 shows an example of an SEM photograph of the sample mill ground product. The composition of the sample mill crushed product measured by EDX was Ga:Co=1.1:5.0 in atomic ratio, and the oxygen content was 1.0 mass%. In addition, the volume-based cumulative 10% particle diameter D10 of the sample mill crushed product measured by the laser diffraction / scattering method was 2 μm, the cumulative 50% particle diameter D50 was 13 μm, and the cumulative 90% particle diameter D90 was 44 μm.
[0033] (iii) Planetary ball milled products A part of the hammer mill-ground product was ground in a planetary ball mill (P-7, manufactured by Fritsch) placed in a sealed container under a nitrogen atmosphere to obtain a planetary ball mill-ground product. FIG. 3 shows an example of an SEM photograph of a product ground by the planetary ball mill. The composition of the planetary ball milled product measured by EDX was Ga:Co=1.1:5.0 in atomic ratio, and the oxygen content was 1.3 mass%. Furthermore, the volume-based cumulative 10% particle diameter D10 of the planetary ball milled product measured by the laser diffraction / scattering method was 3 μm, the cumulative 50% particle diameter D50 was 10 μm, and the cumulative 90% particle diameter D90 was 40 μm.
[0034] FIG. 4 shows particle size distribution curves of the above-mentioned hammer mill pulverized product, sample mill pulverized product, and planetary ball mill pulverized product.
[0035] (X-ray diffraction pattern measurement) X-ray diffraction patterns were measured for each of the above hammer mill-ground, sample mill-ground, and planetary ball mill-ground powders using an X-ray diffractometer (Rigaku, Ultima IV) under conditions of Cu-Kα radiation, tube voltage of 40 kV, tube current of 40 mA, measurement step of 0.02 degrees, and scan speed of 2 degrees / min. The X-ray diffraction patterns are shown in Figure 5. All of the ground products exhibited the diffraction pattern of hexagonal GaCo5 crystals, and it was confirmed that the powders were composed of a nearly single-phase GaCo5 crystal phase.
[0036] (Measurement of powder magnetic properties) The magnetic properties of each powder sample, crushed by the hammer mill, crushed by the sample mill, and crushed by the planetary ball mill, were measured at room temperature using a VSM (Model-5, manufactured by Toei Kogyo Co., Ltd.). The measurement conditions were a maximum applied magnetic field of 6 T and a sweep speed of 1 min / FS. The results showed that the magnetization of each crushed product was not saturated in a magnetic field of 6 T, and the magnetization in a magnetic field of 6 T was 20.0 A m for the hammer mill crushed product. 2 / kg, and the sample mill crushed product was 21.3 A m 2 / kg, and the product ground in the planetary ball mill was 21.3 A m 2 The coercive force was 0.74 T (589 kA / m) for the hammer mill crushed product, 1.48 T (1178 kA / m) for the sample mill crushed product, and 1.86 T (1480 kA / m) for the planetary ball mill crushed product. FIG. 6 shows magnetization curves of the above hammer mill pulverized product, sample mill pulverized product, and planetary ball mill pulverized product.
[0037] (Preparation of conductive compact) The conductive powder compacts were prepared by using the above-mentioned hammer mill crushed product, sample mill crushed product, and planetary ball mill crushed product as described above. Approximately 5 g of each crushed powder was placed in a cylinder of a cylindrical graphite cell with an inner diameter of 10 mm, and a pressure of 90 MPa (7.065 kN) was applied by the upper and lower pistons. The powder was heated in a discharge plasma sintering apparatus under a vacuum atmosphere of approximately 1 Pa to obtain a cylindrical sintered body with a diameter of 10 mm and a height of approximately 8 mm. The heat pattern was to raise the temperature to 500°C, hold it at 500°C for 10 minutes, and then cool.
[0038] (Measurement of the anomalous Nernst effect) A rectangular parallelepiped sample with a length (L1) of approximately 8.0 mm, width (W) of approximately 1.5 mm, and thickness (H) of approximately 0.5 mm was cut out from the above conductive molded body (sintered body). Figure 7 shows the attachment positions of the terminals for measuring electromotive force and the probe for measuring temperature, as well as the directions of heat flow and magnetic field application. Terminals 2a and 2b for measuring electromotive force were attached with conductive epoxy adhesive to the center positions of the opposing sides of the Nernst effect measurement sample 1, so that the voltage (V) generated between both terminals could be measured with a voltmeter. This voltage is generated by the anomalous Nernst effect, so V ANE Temperature measurement probes were attached with conductive epoxy adhesive to two locations (positions indicated by symbols 31 and 32) on the top surface of sample 1 with a gap of 5.0 mm (L2) between them, so that the temperature difference ΔT between them could be monitored. A magnetic field was applied in the thickness direction of the sample while a heat flow was generated in the longitudinal direction of the sample in a physical property measurement system PPMS device manufactured by Quantum Design, and the electromotive force generated between both ends of the sample in the width direction was measured at room temperature (300 K). The black arrow (symbol 4) in Figure 7 indicates the direction of heat flow in the sample. After temperatures T1 and T2 became stable, a magnetic field was applied to the sample, and a voltage V ANE The magnetic field was swept between 3T and -3T and between -3T and 3T. The Nernst coefficient S is calculated using the following formula (1): ANE (μV / K) was calculated. S ANE (μV / K)=V ANE (V) / W / ΔT(K) / L2…(1) Where: V ANE : Electromotive force generated at both ends of the sample in the width direction (V), W: width of sample (mm) ΔT: Temperature difference between the two temperature probe mounting positions (K), L2: The distance between the two temperature probes in the longitudinal direction of the sample (mm), It is.
[0039] The results are shown in Table 1. The measurement results of the Nernst coefficient for the conductive compact using the sample mill pulverized product are shown in Fig. 8. In this example, the Nernst coefficient at a temperature of 300 K with no magnetic field applied (zero magnetic field) was 0.4 μV / K. It has been confirmed that the conductive compact of powder containing the intermetallic compound GdCo5 as the main component according to the present invention has a coercive force exceeding 0.5 T in a measurement of the Nernst coefficient, and exhibits the anomalous Nernst effect in zero magnetic field.
[0040] [Table 1] [Explanation of symbols]
[0041] 1. Sample for measuring the Nernst effect 2a, 2b Electromotive force measurement terminal 31, 32 Temperature measurement position 4. Heat flow direction in the sample 5. Magnetic Field Direction
Claims
1. Intermetallic compound GdCo 5 A powder mainly composed of the above, wherein in a volume-based particle size distribution measured by a laser diffraction / scattering method, the cumulative 50% particle diameter D50 is 1 to 150 μm and the cumulative 90% particle diameter D90 is 250 μm or less.
2. The molten metal of the Gd-Co alloy is solidified to produce the intermetallic compound GdCo. 5 an alloy ingot preparation step for obtaining an alloy ingot having the above-mentioned main component; a crushing step of crushing the alloy block to obtain a powder; The method for producing metal powder according to claim 1, comprising the steps of:
3. Intermetallic compound GdCo 5 A conductive compact made of powder with this as the main component.
4. The intermetallic compound GdCo 5 The powder mainly composed of the conductive molded body according to claim 3 has a cumulative 50% particle diameter D50 of 1 to 150 μm and a cumulative 90% particle diameter D90 of 250 μm or less in a volume-based particle size distribution measured by a laser diffraction / scattering method.
5. Intermetallic compound GdCo 5 4. The conductive molded body according to claim 3, which is a sintered body of a powder containing the above as a main component.
6. 4. The conductive molding according to claim 3, which exhibits a Nernst coefficient of 0.2 μV / K or more at a temperature of 300 K in the absence of an applied magnetic field.
7. A thermoelectric conversion element using the conductive molded article according to any one of claims 3 to 6.
Citation Information
Patent Citations
Composite sensor
JP2020153668A
Weil antiferromagnetic powder and thermoelectric conversion element using the same
JP2021145116A
POWDER OF Co-Mn-Ga SYSTEM ALLOY, CONDUCTIVE MOLDING, MANUFACTURING METHOD THEREOF, AND THERMOELECTRIC ELEMENT
JP2023002425A
Thermoelectric conversion element and thermoelectric conversion device
WO2019009308A1